PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SKALA MATEMATIKA SISWA KELAS V - Trisna Nugraha; Siti Nur Azizah Puji Ayu Lestari (Universitas PGRI Adi Buana Surabaya, 2023)
Learning mathematics in grade V elementary schools in general still maximizes the work of teachers and pays little attention to student involvement in learning because it still uses the direct method where mastery is focused on the teacher. This certainly makes student activity in learning and student mathematics learning outcomes less than optimal. In order to solve problems that can increase student performance, activities, and learning outcomes, Problem Based Learning (PBL) is implemented, so the research aims to describe whether the implementation of problem-based learning models (PBL) can be effective in enhancing student performance and learning outcomes in learning mathematics material Scales and Plans for class V SD. The study implementation is guided by the syntax of the problem-based learning model (PBL) including 1) problem orientation; 2) student organizations; 3) guiding individual or group investigations; 4) developing and presenting results; 5) analyze and evaluate. This study was conducted using the One-shot Case Study experimental research design, with 28 fifth grade elementary school students as subjects. Data collection techniques were carried out through tests, observation and documentation studies. The results showed that the performance and results of students' mathematics learning in problem-based learning were interpreted in high criteria with a percentage range of 84,88%-92,12%. This shows that problem-based learning (PBL) as a constructivist learning can provide space and opportunities for students to participate actively in learning by using problem-solving group discussion learning designs, so that students pay attention to accuracy and attitude in the entire series of PBL learning.